THE ROLE OF INSURTECH IN IMPROVING ACCESS TO DIGITAL INSURANCE SERVICES A STUDY ON THE QOALA APPLICATION - Zikrillah iky; Vira mauliana; Muhammad Fauzan (Indragiri Research Center (ingreat), 2025)
The development of digital technology is driving the transformation of insurance services through the emergence of Insurance Technology (InsurTech). This study aims to analyze the role of InsurTech in increasing access to digital insurance services through the Qoala application. The study used a qualitative approach with interview and observation methods. The results show that the Qoala application provides convenience, efficiency, and transparency in digital insurance services and increases public insurance inclusion. However, digital insurance literacy is still needed to minimize the risks of using digital services. Thus, InsurTech plays a crucial role in the modernization of insurance services in Indonesia.